Música, ruído, interferência e diluição: as trilha musicais de Livio Tragtenberg em Latitude Zero (2000), Contra Todos (2004) e Filmefobia (2008) - Mendoza, Pablo Francisco Menten (2019)
This research aims to broach Livio Tragtenberg's musical creation for contemporary Brazilian cinema. Throughout his career, the composer has teamed up with directors with challenging proposals such as Julio Bressane and Tata Amaral. In his compositions we perceive intriguing musical / sound paths so that these sounds do not go unnoticed in the middle of the film, and they also establish significant relationships with the work in which the music is inserted. The dissertation proposes investigate how Livio Tragtenberg articulates different ideas and sounds in certain filmic contexts. For that, study's object comprises three movies: Latitude Zero, by Toni Venturi (2000); Contra Todos (2003), by Roberto Moreira, and Filmefobia (2009), by Kiko Goifman. These works were chosen because they contain different language proposals that directly implied the approach used by the composer, which does not mean his works do not have a "signature", on the contrary. Although the composer “adapts” to each film, it is possible to find relevant singularities both in the sonorities and in the relation that music establishes with the other elements of the narrative.